The effect of lunasin on inhibition of KI67, BCL-2 and C-MYC expression in azoxymethane and dextran sodium sulfate induced mice colon - Kusmarid, Kusmardi; Putra, Ahmat Rediansya; Kodariah, Ria (Penerbit Universiti Kebangsaan Malaysia, 2023)
Treatment of cancer using medicinal-plant based has been important due to minimal side effects, high efficiency and low cost. Lunasin from soybean is known as potential chemopreventive agent. This study aimed to study and investigate the proteins involved in the mechanisms of action of lunasin underlie its chemopreventive effects in Azoxymethane (AOM) and Dextran Sodium Sulfate (DSS) induced mice. A total 30 BLAB/c mice were separated into six groups. In five of the groups - a negative control group, positive control group, and three intervention groups - carcinogenesis was induced with AOM and DSS; the sixth group received no interventions. Lunasin were given in different doses of Low Dose Lunasin (75 mg/kgBW), Moderate Dose Lunasin (150 mg/kgBW), and High Dose Lunasin (200 mg/kgBW) to intervention groups. Immunohistochemistry was conducted to measure Ki67, C-myc, and Bcl-2 expressions from the distal colons of mice that had been sacrificed. The samples were microscopically assessed and photographed, and cell counts were performed using the Image J application. Further, the H-score method was used to quantify of Ki67, C-myc and Bcl-2 expressions. The results of this show that there is significant differences between the negative control and the intervention groups were found at the 75 mg/kgBW and 150 mg/kgBW (p < 0.05) lunasin dosage levels. This demonstrates that Lunasin inhibits proliferation and induces apoptosis in the colon mice induced by AOM and DSS.